Synthesis, characterization, and investigation of some properties of the new symmetrical bisimine Ni(II), Zn(II), and Fe(III) complexes derived from the monoimine ligand. (12th April 2021) - Dilmen Portakal, Eylem; Kaya, Yeliz; Demirayak, Emire; Karacan Yeldir, Elif; Erçağ, Ayşe; Kaya, İsmet
Abstract : The new symmetrical bisimine (ONNO donor, salen type) Ni(II), Zn(II), and Fe(III) complexes were synthesized in one step from metal ions and monoimine ligand (HL: 4‐amino‐3‐{[(2‐hydroxynaphthalen‐1‐yl)methylidene]amino}phenyl)(phenyl)methanone). The complexes were characterized by analytical, spectral, conductance, magnetic, and thermal data. According to these analysis results, while the bisimine ligand, spontaneously forming during complexation, is attached to the metal by two nitrogen atoms and two phenolic oxygen atoms (N2 O2 ) in all complexes, in the Fe(III) complex, the fifth coordination is completed by the chlorine molecule. A square pyramidal geometry for [FeLCl] and a square planar geometry for [NiL], [ZnL] were proposed. The three‐dimensional structure of [FeLC1] was also evaluated by single‐crystal X‐ray diffraction, and the square pyramidal structure was clearly revealed. The molar conductivity data of the complexes confirmed their nonelectrolytic nature. Poly(imine) (PL) was obtained by the oxidative polymerization reaction of HL, and some of its properties were investigated. The electrochemical properties of the ligand and the complexes were studied by means of cyclic voltammetry. Highest and lowest occupied molecular orbital (HOMO‐LUMO) energy levels and electrochemical band gaps were calculated. The thermogravimetric analysis (TGA) and differential thermal analysis (DTA) of the synthesized compounds were carried out. TGA results showed that the thermal stability of the complexes is high. The solid‐state electrical conductivities of the iodine doped states of the synthesized compounds were measured by the four‐point probe technique. PL has approximately 35 times higher electrical conductivity than the HL and complexes. Fluorescence‐sensor properties of HL were also investigated and predicted that HL could be a selective fluorescence probe for Pb 2+ . Abstract : New symmetrical bisimine Ni(II), Zn(II), and Fe(III) complexes were synthesized and characterized. Thermogravimetric, electrical, and electrochemical properties of the synthesized compounds were investigated. The single‐crystal structure of Fe(III) complex was determined by X‐ray diffraction method.